Wrap & Plant Technology: An Innovative and Cost-Effective Method for Seed Yam Treatment for Nematode Control in Fields. Issue 5 (25th May 2022) - H., H.; Affokpon, Affokpon; A., A.; Badou, Badou; A., A.; Guenther, Guenther; H., R.; Mathew, Mathew; R., R.; Sit, Sit; L., T.; Byrd, Byrd; et al.
No abstract available